12 angry men - Fonda, Henry; Rose, Reginald; Lumet, Sidney; MGM Home Entertainment Inc. (Santa Monica, CA : MGM Home Entertainment Inc., 2001)
Depicts a jury of men who must decide the fate of a teenage boy who has murdered his abusive father. The jurors are from all walks of life, and bring with them their own opinions, prejudices, fears, and personal demons
Based on the play by Regionald Rose
Editing, Carl Lerner ; music, Kenyon Hopkins ; director of photography, Boris Kaufman
Cast : Henry Fonda, Lee J. Cobb, Ed Begley, E.G. Marshall, Jack Warden, Martin Balsam, John Fiedler, Jack Klugman, Edward Binns, Joseph Sweeney, George Voskovec, Robert Webber
Keywords: Trials (Murder) -- United States -- Drama; Jury -- United States -- Drama; Abused children -- United States -- Drama; Parricide -- United States -- Drama; Capital punishment -- United States -- Drama